Digital imaging : - Galer, Mark (Elsevier, 2005)
Marketing Research Essentials, 4th Edition is filled with cases, chapter-opening vignettes, marketing research war stories, and ethical dilemmas. The text connects the materials to the real world of marketing research, as it's practiced in today's top firms. Both authors bring a combined 40 years of marketing research experience to the new edition. This fourth edition continues to present marketing research through the eyes of a manager using, or purchasing marketing research information